DESEMPENHO ZOOTÉCNICO DE CURIMBAS EM SISTEMA DE RECIRCULAÇÃO DE ÁGUA E AQUAPONIA. - MENDEZ, Victor Hugo Benassi; NETO, Nilton de Magalhães; ACUNHA, Rubia Mara Gomes; WANDERLEY, Alysson Martins; ALMEIDA, Rômullo Guilherme dos Santos; MELDAU, Cristiane de Campos (ANAIS DO ENIC, 2024)
-